(3eTcGI GdCfhGQ hNRGfI GdCSQGQs - (3YHO Gddg Hf CMeO Hf YHO GdMejO GdMSjfjs ((3YHO GdefYe Hf eMeO Hf Ydj Hf EHQGgje GdTgjQ HaQSGfs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEf GdYdhe eQGHJ aj GdYbhd hJHgG Gddg YR hL ajgG aefg eG gh ebOe Ydi LejY GdeYdheGJ hgj eQJHI (B...s
(3BNQgG (B:s
... (3hYGTJ Mhi HYOg SfI Ke eGJJ hOafJ eY RhLgG BOe Ydjg GdSdGe hde jeJ BOe MJi HdZ hdOg hhdO hdOg CQHYjf CdaG hcGf Chd TjA Ccd aj GdLfI GdYfH hBNQ TjA Ccd GdYfH hYGT JSYeGFI hKdGKhf hGddg CYde (B. (3Jes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJGQjNs